A validation study of a consecutive interpreting test using many-facet Rasch analysis - Zhao, Nan (Frontiers in Communication, 2023)
Validation is the process of conducting a validity study on a test, gathering evidence to support inferences made based on test scores. Using many-facet Rasch analysis this paper validates the result of a consecutive interpreting test from four aspects: rating scale, raters, examinees and interpreting tasks. The study also identifies factors that affect the test results through bias analysis. The results of this analysis show that: (1) this analytical rating scale and task design can effectively reflect the examinees' interpreting competence, thus making it suitable for validating interpreting assessments; (2) one of the sub-scales: interpreting skills and manners, has a slightly negative effect on the overall validity of the assessment, making further revision on this sub-scale desirable.